2011
DOI: 10.1128/jb.05733-11
|View full text |Cite
|
Sign up to set email alerts
|

Effects on Transcription of Mutations in ygjD , yeaZ , and yjeE Genes, Which Are Involved in a Universal tRNA Modification in Escherichia coli

Abstract: The Escherichia coli ygjD gene is critical for the universal tRNA modification N 6 -threonylcarbamoyladenosine, together with two other essential genes, yeaZ and yjeE. This study showed that the transcription of the thr and ilv operons in ygjD mutants was increased through the inhibition of transcription attenuation and that dnaG transcription was reduced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 17 publications
1
15
0
Order By: Relevance
“…Another possibility is that the protein levels for each gene are regulated at a post-translational level and could not be determined by our present experiments. Our qPCR and ilv promoter- lux reporter experiments further confirmed the 2D-DIGE and mass spectrometry results and indicated the transcriptional modulation of ilv - leu operon by Gcp in S. aureus , which is consistent with previous report that the depletion of Gcp homolog, YgjD, in E. coli increases the transcription of the thr and ilv operons [27]. Our qPCR assays revealed that Gcp has a similar influence on the transcriptional level of ilvD , leuA , and ilvA , but has no impact on ilvE , which lies outside of the ilv - leu operon in the S. aureus chromosome.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Another possibility is that the protein levels for each gene are regulated at a post-translational level and could not be determined by our present experiments. Our qPCR and ilv promoter- lux reporter experiments further confirmed the 2D-DIGE and mass spectrometry results and indicated the transcriptional modulation of ilv - leu operon by Gcp in S. aureus , which is consistent with previous report that the depletion of Gcp homolog, YgjD, in E. coli increases the transcription of the thr and ilv operons [27]. Our qPCR assays revealed that Gcp has a similar influence on the transcriptional level of ilvD , leuA , and ilvA , but has no impact on ilvE , which lies outside of the ilv - leu operon in the S. aureus chromosome.…”
Section: Discussionsupporting
confidence: 92%
“…This new finding indicates one conserved function between the staphylococcal Gcp and the E. coli homolog YjgD. It is possible that Gcp mediates the transcription of the ilv - leu operon through the t6A modification pathway, as uncharged tRNA act as a positive regulatory factor to increase gene expression during amino acid limitation [32] and the lack of t6A modification may interfere with T-box dependent regulation of the ilv operon [27]. In addition, qPCR revealed that during the depletion of Gcp the increased transcription levels of ilvD , leuA and ilvA genes in one polycistronic operon exhibited significant variations.…”
Section: Discussionmentioning
confidence: 80%
“…This suggested that these genes belonged to a complex regulatory network (Msadek, ), but the rstA suppression phenotype has never been really explained. Overexpression of other genes such as rho , encoding a transcription terminator, or dnaG , encoding DNA primase, have also been reported to suppress the essentiality phenotype caused by depletion of the t 6 A synthesis enzymes (Hashimoto et al ., 2011; 2013; Bergmiller et al ., ), but it is unknown if t 6 A is absent from tRNA isolated from these suppressor strains. Lack of t 6 A‐modificed tRNA in these strains would compromise the development of antibacterials targeting the enzymes of t 6 A machinery, as resistant clones could be selected at a high frequency.…”
Section: Introductionmentioning
confidence: 99%
“…Their functional interaction was first suggested because strains that conditionally express these three genes were complemented by a multicopy plasmid carrying the rstA gene, which codes for a response regulator of a two‐component system (Handford et al ., ). The functional interaction was also suggested by the results of multicopy suppression: the yeaZ ts mutation was suppressed by yjeE or ygjD multicopy plasmids, the ygjD ts mutant was suppressed by yjeE or yeaZ multicopy plasmids, and the yjeE ts mutant was suppressed by the yeaZ multicopy plasmid (Hashimoto et al ., ). Physical interactions between YeaZ and YjeE and between YeaZ and YgjD and the proteolysis of purified YgjD mediated by purified YeaZ were shown (Handford et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Furthermore, the four proteins (YgjD, YrdC, YjeE and YeaZ) were shown to be both necessary and sufficient for t 6 A biosynthesis in vitro (Deutsch et al ., ). In ygjD ts mutants, transcription of the thr and ilv operons was increased indirectly through the inhibition of transcriptional attenuation by defective translation of the leader peptides (Hashimoto et al ., ).…”
Section: Introductionmentioning
confidence: 97%